Analisis Pengaruh Pendapatan Daerah, Belanja Daerah dan Pembiayaan Daerah Terhadap Pajak Daerah di Sumatra Utara - Luffi Nabila Siregar; Shita Tiara (Forum Kerjasama Pendidikan Tinggi, 2022)
This study aims to determine how to determine the effect of local taxes on regional income, regional spending and regional financing in North Sumatra. The type of research used in this research is descriptive qualitative. The analysis technique used in this research is to conduct field studies and literature studies. Based on the results of research that has been carried out, the contribution of local tax revenue has increased in 2018-2019, while in 2020-2021 it has decreased, affecting the regional income of North Sumatra. As well as Regional tax revenues contribute to increasing local revenue, regional spending and regional financing in North Sumatra.